Maximizing distributed energy resource hosting capacity of power system in South Korea using integrated feeder, distribution, and transmission system - Widiputra, Victor; Kong, Junhyuk; Yang, Yejin; Jung, Jaesung; Broadwater, Robert (Energies, 2020)
Intermittent power generated from renewable distributed energy resource (DER) can create voltage stability problems in the system during peak power production in the low demand period. Thus, the existing standard for operation and management of the distribution system limits the penetration level of the DER and the amount of load in a power system. In this standard, the hosting capacity of the DER is limited to each feeder at a level where the voltage problem does not occur. South Korea applied this standard, thereby making it hard to achieve its DER target. However, by analyzing the voltage stability of an integrated system, the hosting capacity of DER can be increased. Therefore, in this study, the maximum hosting capacity of DER is determined by analyzing an integrated transmission and distribution system. Moreover, the fast voltage stability index (FVSI) is used to verify the determined hosting capacity of DER. For this, the existing interconnection standard of DER at a feeder, distribution system, and transmission system level is investigated. Subsequently, a Monte Carlo simulation is performed to determine the maximum penetration of the DER at a feeder level, while varying the load according to the standard test system in South Korea. The actual load generation profile is used to simulate system conditions in order to determine the maximum DER hosting capacity.
Keywords: Distributed energy resource; Distributed Energy Resources; Distribution systems; Fast voltage stability indices; Interconnection standards; Operation and management; Transmission and distribution systems; Transmission systems; Distributed energy resource (DER); Fast voltage stability index (FVSI); Monte Carlo Simulation (MCS)